Optimizing hepatectomy for hepatocellular carcinoma in Asia-patient selection and special considerations - Kotewall, Clarence Nicholas; Cheung, Tan To (Translational Gastroenterology and Hepatology, 2018)
Hepatocellular carcinoma (HCC) is a common affliction in Asia. The treatment of HCC depends on the tumor status as well as the underlying liver function. Resection is the cornerstone of surgical management of HCC. For those unfit to undergo resection, local ablative therapy is a viable alternative. For patients with multiple small unresectable HCCs, liver transplantation offers another option, having the simultaneous benefit of removing the cancer in addition to replacing the pre-malignant and cirrhotic liver together. However, the paucity of liver grafts limits the applicability of this operation. In assessing for the appropriate treatment, the traditional TNM staging is not widely applied to HCC. Conventionally, doctors in the West have relied on the Barcelona staging system. Asian surgeons, on the other hand, have long adopted a more aggressive approach for their patients. Borne out of the need for a system which better suited Asian patients, the Hong Kong guidelines have been established. For the surgical resection of HCC, considerations must take into account issues regarding the tumor, the underlying liver and the patient. For the tumor, the size, the presence vascular invasion and presence of extra-hepatic metastasis will determine operability. Another important issue is the liver function and, by extension, the estimated residual liver volume after resection. Thirdly, patient factors i.e., fitness to undergo general anesthesia must be properly assessed. With improved surgical technique and better patient selection, peri-operative morbidity and long-term survival results after operation have improved drastically over the past decades.